2010
DOI: 10.3390/md8122871
|View full text |Cite
|
Sign up to set email alerts
|

Potential Anti-HIV Agents from Marine Resources: An Overview

Abstract: Human immunodeficiency virus (HIV) infection causes acquired immune deficiency syndrome (AIDS) and is a global public health issue. Anti-HIV therapy involving chemical drugs has improved the life quality of HIV/AIDS patients. However, emergence of HIV drug resistance, side effects and the necessity for long-term anti-HIV treatment are the main reasons for failure of anti-HIV therapy. Therefore, it is essential to isolate novel anti-HIV therapeutics from natural resources. Recently, a great deal of interest has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 113 publications
(113 reference statements)
0
118
0
1
Order By: Relevance
“…Some of these plantsderived antiretroviral therapies have been shown to have inhibitory activities against several HIV-1 processes, including viral entry, reverse transcription, replication, integration, virus maturation and virion budding. Some of these compounds have been clinically tested, with favourable results (Asres et al, 2005;Park et al, 2009;Vo and Kim, 2010;Jiang et al, 2010;Filho et al, 2010;Sing and Bodiwala, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these plantsderived antiretroviral therapies have been shown to have inhibitory activities against several HIV-1 processes, including viral entry, reverse transcription, replication, integration, virus maturation and virion budding. Some of these compounds have been clinically tested, with favourable results (Asres et al, 2005;Park et al, 2009;Vo and Kim, 2010;Jiang et al, 2010;Filho et al, 2010;Sing and Bodiwala, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many research groups are being required to search for novel anti-HIV agents compatible to those of developed countries. Marine-based natural products that have chemically diverse and unique structures have received attention as sources for the development of new anti-HIV agents (Vo and Kim, 2010). Marine materials such as phlorotannins, sulfated chitoolifosaccharides, sulfated polysaccharides, and lectin have been reported to have anti-HIV activities.…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional benefits of fish consumption are due to the presence of proteins, unsaturated essential fatty acids, minerals (for example, calcium, iron, selenium and zinc), and vitamins, namely Vitamin A, B3, B6, B12, E and D. Research has also shown that peptides derived from fermented fish following enzymatic treatment may be useful therapeutics for the treatment of many common acute and chronic diseases such as viral infections, hypertension, cancer and Alzheimer's disease [7]. Fish collagen may also be used in bone treatment as an alternative to mammalian collagen which is known to be immunogenic [8].…”
Section: Marine Fishmentioning
confidence: 99%